The Effect of Dietary Candlenut Powder on Blood Profile and Meat Cholesterol Content of Broilers - Putri, Fitria Tridyana; Sudjarwo, Edhy; Sjofjan, Osfar (Jurnal Agripet, 2018)
ABSTRACT. The purpose of this research was to investigate the use of candlenut powder (Aleurites mollucana (L.) Willd.) as feed additive on blood profile and meat cholesterol content of broilers. Materials used in this research were 200 day-old broiler chicks. Research method was in vivo on Completely Randomized Design with 5 treatments (P0 = basal diets only, P1 = basal diets + 0.25% candlenut powder, P2 = basal diets + 0.5% candlenut powder, P3 = basal diets + 0.75% candlenut powder, P4 = basal diets + 1% candlenut powder), each treatment was replicated 5 times. Variables measured were blood profile (erythrocyte, hemoglobin, mean corpuscular volume, and mean corpuscular hemoglobin) and meat cholesterol content. Data were analyzed by using Analysis of Variance. Data with significant different effects were further analyzed by using Duncans Multiple Range Test. The results showed that candlenut powder usage as feed additive had a highly significant effect on (P0.01) erythrocyte and hemoglobin levels. Candlenut powder also significantly affect (P0.05) mean corpuscular hemoglobin (MCH), but did not significantly affect (P0.05) mean corpuscular volume (MCV) levels. Broilers fed candlenut powder had lower (P0.01) meat cholesterol content compared to those fed basal diets only. It might be concluded that the use of candlenut powder as feed additive at the level of 1% is safely recommended to give better blood profile and reduce meat cholesterol content of broilers.Pengaruh penambahan tepung biji kemiri terhadap profil darah ayam pedaging dan kandungan kolesterol dagingABSTRAK. Tujuan penelitian ini untuk mengevaluasi pemanfaatan tepung biji kemiri (Aleurites mollucana (L.) Willd.) sebagai aditif pakan terhadap profil darah dan kandungan kolesterol daging ayam pedaging. Materi yang digunakan adalah 200 ekor day old chicks (DOC) ayam pedaging. Metode penelitian menggunakan percobaan in vivo pada Rancangan Acak Lengkap (RAL) dengan 5 perlakuan (P0 = pakan basal, P1 = pakan basal + 0.25% tepung biji kemiri, P2 = pakan basal + 0.5% tepung biji kemiri, P3 = pakan basal + 0.75% tepung biji kemiri, P4 = pakan basal + 1% tepung biji kemiri), setiap perlakuan diulang sebanyak 5 kali. Data dianalisis menggunakan analisis variansi (ANOVA) perbedaan yang signifikan dilanjutkan dengan Uji Jarak Berganda Duncans. Hasil penelitian menunjukkan bahwa pemanfaatan tepung biji kemiri sebagai aditif pakan memberikan perbedaan yang sangat nyata (P0,01) terhadap jumlah eritrosit dan hemoglobin. Tepung biji kemiri juga memberikan pengaruh yang nyata (P0,05) terhadap mean corpuscular hemoglobin (MCH), tetapi tidak memberikan pengaruh yang nyata terhadap mean corpuscular volume (MCV) darah ayam. Ayam pedaging yang diberi pakan dengan penambahan tepung biji kemiri memiliki kandungan kolesterol daging yang lebih rendah (P0,01) dibandingkan dengan yang hanya diberi pakan basal. Kesimpulan dari penelitian ini adalah bahwa penambahan tepung biji kemiri sebanyak 1% dapat memberikan profil darah yang lebih baik dan efektif untuk menurunkan kandungan kolesterol daging ayam pedaging.ABSTRACT. The purpose of this research was to investigate the use of candlenut powder (Aleurites mollucana (L.) Willd.) as feed additive on blood profile and meat cholesterol content of broilers. Materials used in this research were 200 day-old broiler chicks. Research method was in vivo on Completely Randomized Design with 5 treatments (P0 = basal diets only, P1 = basal diets + 0.25% candlenut powder, P2 = basal diets + 0.5% candlenut powder, P3 = basal diets + 0.75% candlenut powder, P4 = basal diets + 1% candlenut powder), each treatment was replicated 5 times. Variables measured were blood profile (erythrocyte, hemoglobin, mean corpuscular volume, and mean corpuscular hemoglobin) and meat cholesterol content. Data were analyzed by using Analysis of Variance. Data with significant different effects were further analyzed by using Duncans Multiple Range Test. The results showed that candlenut powder usage as feed additive had a highly significant effect on (P0.01) erythrocyte and hemoglobin levels. Candlenut powder also significantly affect (P0.05) mean corpuscular hemoglobin (MCH), but did not significantly affect (P0.05) mean corpuscular volume (MCV) levels. Broilers fed candlenut powder had lower (P0.01) meat cholesterol content compared to those fed basal diets only. It might be concluded that the use of candlenut powder as feed additive at the level of 1% is safely recommended to give better blood profile and reduce meat cholesterol content of broilers.